2020
DOI: 10.1007/s40268-020-00327-y
|View full text |Cite
|
Sign up to set email alerts
|

A GFR-Based Method to Predict the Effect of Renal Impairment on the Exposure or Clearance of Renally Excreted Drugs: A Comparative Study Between a Simple GFR Method and a Physiologically Based Pharmacokinetic Model

Abstract: Objective The objective of this study was to compare the predictive performances of a glomerular filtration rate (GFR) model with a physiologically based pharmacokinetic (PBPK) model to predict total or renal clearance or area under the curve of renally excreted drugs in subjects with varying degrees of renal impairment. Methods From the literature, 11 studies were randomly selected in which total or renal clearance or area under the curve of drugs in subjects with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The clinical assessment of potential DDIs between ARVs and commonly used co‐medications in people living with HIV and renal impairment is vital to prevent the development of ESRD, AKI, and CKD, as well as to prevent ineffective ARV treatment 58 . Although outside the scope of this review, renal impairment has been reported to impact the glomerular filtration rate, affecting overall drug clearance and, in turn, potential DDI magnitudes through changes in perpetrator and/or victim concentrations 59 . Furthermore, a previous review highlighted the impact of kidney disease on drug metabolism and transport 60 .…”
Section: Renal Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical assessment of potential DDIs between ARVs and commonly used co‐medications in people living with HIV and renal impairment is vital to prevent the development of ESRD, AKI, and CKD, as well as to prevent ineffective ARV treatment 58 . Although outside the scope of this review, renal impairment has been reported to impact the glomerular filtration rate, affecting overall drug clearance and, in turn, potential DDI magnitudes through changes in perpetrator and/or victim concentrations 59 . Furthermore, a previous review highlighted the impact of kidney disease on drug metabolism and transport 60 .…”
Section: Renal Impairmentmentioning
confidence: 99%
“… 58 Although outside the scope of this review, renal impairment has been reported to impact the glomerular filtration rate, affecting overall drug clearance and, in turn, potential DDI magnitudes through changes in perpetrator and/or victim concentrations. 59 Furthermore, a previous review highlighted the impact of kidney disease on drug metabolism and transport. 60 Experimental models of ESRD demonstrated decreased activity and downregulation of hepatic and intestinal metabolic enzymes and transporters.…”
Section: Renal Impairmentmentioning
confidence: 99%
“…(2012) studied the same phenomena by considering the impact of CKD on the metabolic and transporter‐mediated clearance of sildenafil, repaglinide, and telithromycin. Apart from these, few modeling attempts were also made with regard to changes in GFR as per severity, stage of disease, and by integrating the effect of CKD on tubular reabsorption and tubular adaptations (Huang & Isoherranen, 2020; Mahmood, 2020; Rasool et al., 2021; Zhou et al., 2019). Upcoming work in this area would be to incorporate changes in the expression and abundance of DMETs within renal or extrarenal tissues (Butrovich et al., 2022; Imaoka et al., 2021) along with the effect of other comorbidities such as age and lifestyle along with CKD (Scotcher & Galetin, 2022).…”
Section: Predictions In Special and Diseased Populationsmentioning
confidence: 99%
“…Recently, Mahmood 19 compared a whole‐body PBPK model with a simple glomerular filtration rate model for the prediction of total and renal clearances of extensively renally excreted drugs in subjects with renal impairment (mild, moderate, and severe) and found that both models provided similar results. The study indicates that to predict total and renal clearances of drugs in subjects with renal impairment, a PBPK model is unnecessary and a simple model that uses just one physiological parameter (glomerular filtration rate) is enough to achieve similar objectives.…”
mentioning
confidence: 99%